Decreasing resection rates for nonmetastatic gastric cancer in Europe and the United States - Huang, Lei; Jansen, Lina; Balavarca, Yesilda; Verhoeven, Rob H. A.; Ruurda, Jelle P.; Eycken, Liesbet Van; Schutter, Harlinde De; Johansson, Jan; Lindblad, Mats; Johannesen, Tom B.; Zadnik, Vesna; Žagar, Tina; et al. (Clinical and translational medicine, 2020)
Background Resection is the cornerstone of curative treatment for many nonmetastatic gastric cancers (GCs), but the population treatment patterns remains largely unknown. This large international population-based study aimed at investigating the treatment patterns and trends for nonmetastatic GC in Europe and the United States and at exploring factors associated with resection. Methods Data of patients with microscopically confirmed primary invasive GC without distant metastasis from the national cancer registries of the Netherlands, Belgium, Sweden, Norway, Slovenia, and Estonia and the US Surveillance, Epidemiology, and End Results (SEER)-18 Program were retrieved. Age-standardized treatment rates were computed and trends were evaluated using linear regression. Associations of resection with patient and tumor characteristics were analyzed using multivariable-adjusted log-binomial regression. Analysis was performed in each country respectively without pooling. Results Together 65 707 nonmetastatic GC patients diagnosed in 2003-2016 were analyzed. Age-standardized resection rates significantly decreased over years in all countries (by 4-24%). In 2013-2014, rates varied greatly from 54 to 75%. Patients with increasing ages, cardia cancers, or cancers invading adjacent structure were significantly less frequently resected. Resection was further associated with sex, performance status, comorbidities, tumor histology, tumor size, hospital type, and hospital volume. Association patterns and strengths varied across countries. After multivariable adjustment, resection rates remained decreasing (prevalence ratio = 0.97-0.995 per year), with decreasing trends consistently seen in various subgroups. Conclusions Nonmetastatic GCs were less frequently resected in Europe and the United States in the early 21st century. Resection rates varied greatly across countries and appeared not to be optimal. Various factors associated with resection were revealed. Our findings can help to identify differences and possibly modifiable places in clinical practice and provide important novel references for designing effective population-based GC management strategies. In Europe and the United States, nonmetastatic gastric cancers were less frequently resected in the early 21st century. Resection rates varied greatly across countries and appeared not optimal. Various factors associated with resection were revealed. Our findings identify differences and possibly modifiable places in clinical practice and provide important novel references for designing effective population-based management strategies.